Succession as a risk process in the survival of a family business: Case of Slovakia - Boris Rumanko; Zuzana Lušňáková; Monika Moravanská; Mária Šajbidorová (Journal of Risk and Financial Management, 2021)
Generational transfer is a risky point in the life cycle of any family business, and thus the succession process should not be underestimated. Family businesses in Slovakia began to appear after 1989, and therefore many of them await the process of generational exchange in the coming years. For this reason, research on generational exchange has been limited. The aim of this paper was to evaluate the attitude of the owners of Slovak family businesses to the succession process and to reveal the key factors that positively or negatively affect this process. A semi-structured interview was selected as a tool for data collection, in which 74 family business owners took part. The findings were evaluated by the text mining method and afterwards transferred to a scatter diagram in concepts. Based on the clusters in the scatter plot, we revealed the key factors that the current owners consider to be a risk in successfully managing generational exchange. We found that only 48.64% of owners started the succession process, which proves the importance of solving the problem in Slovakia.
Keywords: 330; family business; generational exchange; owners; succession